Biomimetic Engineering of a Scavenger‐Free Nitric Oxide‐Generating/Delivering System to Enhance Radiation Therapy - Lin, Yu‐Jung; Chen, Chun‐Chieh; Nguyen, Dang; Su, Huei‐Rou; Lin, Kun‐Ju; Chen, Hsin‐Lung; Hu, Yu‐Jung; Lai, Po‐Liang; Sung, Hsing‐Wen (Small (Weinheim an der Bergstrasse, Germany), 2020)
Nitric oxide (NO) is a potent tumor‐cell radiosensitizer but it can be readily scavenged by hemoglobin (Hb) in vivo. A biomimetic incubator that can generate and deliver NO in a scavenger (Hb)‐free environment to enhance its radiosensitizing effect to maximize its efficacy in radiotherapy is proposed. This NO incubator comprises a poly(lactic‐co‐glycolic acid) (PLGA) hollow microsphere (HM) that contains an NO donor (NONOate) and a surfactant molecule (sodium caprate, SC) in its aqueous core. In acidic tumorous environments, the PLGA shell of the HM allows the penetration of protons from the outside, activating the hydrolytic cleavage of NONOate, spontaneously generating NO bubbles, which are immediately trapped/stabilized by SC. The SC‐stabilized NO bubbles in the HM are then squeezed through the spaces of its PLGA matrices by the elevated internal pressure. Upon leaving the HM, the entrapped NO molecules may passively diffuse through their SC‐stabilized/protected layer gradually to the tumor site, having a long‐lasting radiosensitizing effect and inhibiting tumor growth. The entire process of NO generation and delivery is conducted in a scavenger (Hb)‐free environment, mimicking the development of young ovoviviparous fish inside their mothers' bodies in the absence of predators before birth. The as‐proposed hollow microsphere system may function as an incubator for the generation and delivery of NO in a scavenger‐free environment, analogous to the protection offered by ovoviviparous fish against predation before birth of their offspring. Upon leaving the incubator, the NO molecules may passively diffuse through their protected‐surfactant layer gradually to the tumor site, performing long‐lasting radiosensitization.